Technique for assessing the astringency of persimmon fruit by measuring the liposome aggregation - Kera, Kota; Makino, Shohei; Takeda, Risako; Shimeno, Aoi; Hojo, Masaya; Hamasaki, Sadahiro; Endo, Akihito; Iijima, Masumi; Nakayama, Tsutomu (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2024)
The astringency of persimmon fruits is a significant factor for consumers and the nutritional industry. To date, astringents, such as polyphenols, specifically persimmon condensed tannins, have been assessed using polyphenol quantification assays, such as the Folin–Ciocalteu method, based on their reducing power. However, these methods are influenced by the presence of other reducing substances. In this study, we developed a cost-effective liposome turbidity analysis using a portable visible spectrophotometer based on the interaction between liposomes and astringents. Authentic astringents, such as catechins and theaflavin-3-O-gallate, were analyzed, and their half-maximal effective concentrations (EC50) were calculated. These results indicated that the affinity to the membrane was similar to that of astringency, as determined by sensory analysis. Additionally, the EC50 values of partially purified tannins from non-astringent and astringent persimmons were calculated. In conclusion, we determined the application methods to assess astringent persimmon fruits with and without the removal of astringency.